The effect of Stablecoin on the Jakarta Composite Index (JCI) - Thaifur K. Umar; Johan Fahri; Rusandry Rusandry (AIBPM Publisher, 2025)
This study investigates the effect of stablecoins, particularly Tether (USDT), on the Indonesian capital market represented by the Jakarta Composite Index (JCI). Rooted in blockchain technology evolution and the growing effect of crypto-asset on global markets, this research seeks to examine whether the relatively stable characteristics of stablecoins produce different impacts compared to volatile crypto-asset such Bitcoin (BTC). Using monthly time-series data from October 2018 to October 2024 and applying multiple linear regression analysis, the findings reveal that Stablecoin Price has a negative and significant effect on the JCI, whereas Stablecoin Volume exhibits insignificant effect. This implies that a decrease in stablecoin prices corresponds with an increase in stock index performance, indicating investors’ preference to shift from crypto-assets to equities when stablecoin prices fall. The absence of volume effects further suggests that investors do not perceive stablecoin trading activity as an investment signal due to its low volatility and value stabilization mechanisms pegged to the USD. The study contributes theoretically to the literature on digital asset integration into traditional financial systems and provides practical insights for policymakers and investors in designing regulatory frameworks and diversification strategies in the Indonesian financial market. Keywords: Stablecoin; Tether (USDT); Bitcoin (BTC); Jakarta Composite Index (JCI); Crypto-asset; Blockchain Technology; Capital Market; Portfolio Diversification; Indonesia